2021
DOI: 10.1177/09544054211061961
|View full text |Cite
|
Sign up to set email alerts
|

Performance assessment of energy efficient and eco-friendly turning of Nimonic C-263: A comparative study on MQL and cryogenic machining

Abstract: Nimonic C-263 is predominantly used in the manufacturing of heat susceptible intricate components in the gas turbine, aircraft, and automotive industries. Owing to its high strength, poor thermal conductivity, the superalloy is difficult to machine and causes rapid tool wear during conventional machining mode. Moreover, the unpleasant machining noise produced during machining severely disrupts the tool engineer’s concentration, thereby denying a precise and environment friendly machining operation. Hence, clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…liquid nitrogen cryogen) is one of the most reliable alternative cooling, which creates a safe environment around the operator and a pollution-free atmosphere during operation. 16,17 Due to better control of grinding temperature, liquid nitrogen (LN 2 ), as a coolant, improved the development of defect-free surfaces, higher material removal rates and lower grinding forces in the grinding process. 18 Until now, numerous studies have been performed on the force, specific energy, temperature, surface texture, wheel wear, material removal rate (MRR), residual stress, microhardness and chip morphology related to grinding operations, [19][20][21][22] only some literature are available on difficult-to-machine materials for these parameters under cryogenic grinding processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…liquid nitrogen cryogen) is one of the most reliable alternative cooling, which creates a safe environment around the operator and a pollution-free atmosphere during operation. 16,17 Due to better control of grinding temperature, liquid nitrogen (LN 2 ), as a coolant, improved the development of defect-free surfaces, higher material removal rates and lower grinding forces in the grinding process. 18 Until now, numerous studies have been performed on the force, specific energy, temperature, surface texture, wheel wear, material removal rate (MRR), residual stress, microhardness and chip morphology related to grinding operations, [19][20][21][22] only some literature are available on difficult-to-machine materials for these parameters under cryogenic grinding processes.…”
Section: Introductionmentioning
confidence: 99%
“…liquid nitrogen cryogen) is one of the most reliable alternative cooling, which creates a safe environment around the operator and a pollution-free atmosphere during operation. 16,17 Due to better control of grinding temperature, liquid nitrogen (LN 2 ), as a coolant, improved the development of defect-free surfaces, higher material removal rates and lower grinding forces in the grinding process. 18…”
Section: Introductionmentioning
confidence: 99%
“…The ability of the coolant to intrude into the tool work interface due to high pressure is attributed to the improvement of the aforementioned responses. In the experimental investigations carried out by Jadhav and Mohanty, 10 MQL and cryogenic cooling were compared while machining Nimonic-C263 alloy in terms of surface roughness, tool wear and cutting forces. It was identified that surface roughness and tool life improved by 18.7%, 6.5% respectively while cutting force was reduced by 30% in cryogenic machining compared to MQL.…”
Section: Introductionmentioning
confidence: 99%